Clinical and immunological analysis of measles patients admitted to a Beijing hospital in 2014 during an outbreak in China. Issue 12 (2nd June 2016) - TU, B.; ZHAO, J.-J.; HU, Y.; FU, J.-L.; HUANG, H-H.; XIE, Y.-X.; ZHANG, X.; SHI, L.; ZHAO, P.; ZHANG, X.-W.; WU, D.; XU, Z.; et al.
SUMMARY: At the end of 2013, China reported a countrywide outbreak of measles. From January to May 2014, we investigated the clinical and immunological features of the cases of the outbreak admitted to our hospital. In this study, all 112 inpatients with clinically diagnosed measles were recruited from the 302 Military Hospital of China. The virus was isolated from throat swabs from these patients, and cytokine profiles were examined. By detecting the measles virus of 30 of the 112 patients, we found that this measles outbreak was of the H1 genotype, which is the major strain in China. The rates of complications, specifically pneumonia and liver injury, differed significantly in patients aged <8 months, 8 months to 18 years, and >18 years: pneumonia was more common in children, while liver injury was more common in adults. Pneumonia was a significant independent risk factor affecting measles duration. Compared to healthy subjects, measles patients had fewer CD4 + IL-17 +, CD4 + IFN- γ +, and CD8 + IFN- γ + cells in both the acute and recovery phases. In contrast, measles patients in the acute phase had more CD8 + IL-22 + cells than those in recovery or healthy subjects. We recommend that future studies focus on the age-related distribution of pneumonia and liver injury as measles-related complications as well as the association between immunological markers and measles prognosis.